Comparative study of two different zeolites BEA and ZSM-5 exchanged by copper and iron via the oxidation of phenol by hydrogen peroxide - TALHAOUI, Fatiha; HAMIDI, Fatiha; Medina, Fransisco (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/Purpose: Water pollution by organic compounds such as phenol poses a major environmental risk. This study aims to compare the catalytic efficiency of ZSM-5 and BEA zeolites, doped with iron (Fe) and copper (Cu), for the wet oxidation of phenol using hydrogen peroxide (H₂O₂). Method: BEA and ZSM-5 zeolites were synthesized via hydrothermal methods, then ion-exchanged to incorporate Cu²⁺ and Fe²⁺. The catalysts were characterized using XRD, FTIR, SEM, and XPS. Phenol oxidation was carried out at 80 °C in aqueous medium with an H₂O₂/phenol molar ratio ranging from 10:1 to 15:1. The reaction products were analyzed by HPLC. Results: The crystalline structures of the zeolites were maintained after ion exchange. The metals were well dispersed on the surface. Fe-BEA and Fe-ZSM-5 catalysts showed the highest activity (up to 99% conversion), followed by Cu-BEA (88%) and Cu-ZSM-5 (68%). The pure zeolites exhibited low activity (<10%). The optimal H₂O₂/phenol ratio was 14:1. Fe-BEA proved to be the most effective, combining high activity with enhanced diffusion within the pores. Conclusion: Iron-exchanged zeolites, particularly Fe-BEA, are highly effective catalysts for phenol oxidation in aqueous media, outperforming both copper-doped and pure forms. The porous structure and the nature of the metal are key factors determining catalytic performance.